Desentralisasi Pendidikan;: Studi Implementasi Peraturan Daerah Kabupaten Jembrana Nomor 15 Tahun 2006 Tentang Rintisan Wajib Belajar 12 Tahun - Rohil, Zilfa (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
Decentralization provides innovation for public education in the districts. The local government is a major holder of realization of the program as well as education policies. For example, the 12-year compulsory education program stipulated in a presidential decree has no legal implications for those who do not implement it, because they do not have a strong legal basis. In the Dictrict of Jembrana Bali, 12 years compulsoryeducation have a legal basis based on Jembrana District Regulation number 15 in 2006 concerning piloting of the 12-year compulsory education. This is the positive implications of the decentralization of education. The local government executive demographically closest to the people should be able to realize that pro-people policies so that people feel the real impact of public policy set. Government Jembranamade innovation in the field of education, by (1) providing opportunities for education broadest, (2) Free education for all public schools students, (3) provide scholarships for students in private schools, from elementary, junior high schools and Universities, and (4) improving teachers capacity.